Towards COBIT-based framework to govern flood management - Othman M.; Ahmad M.N.; Suliman A.; Arshad N.H. (Pacific Asia Conference on Information Systems, 2023)
The worsening condition of floods in Malaysia, in terms of frequency and impact, calls for improvement in all aspects of flood management. In addition to technology enhancement of, and developing expertise, it is hoped that improvement on the governance of flood management could alleviate the problems relating to floods. Governance of flood management aims to address the issues related to flood management by having a well-defined governance structure over processes leading to improving decision making; and efficient management of the data and information (capture, manipulation, and sharing of information) to enable quick and correct decisions to be made. Activities involved in flood management are sequenced into phases which reflect a flood cycle. The COBIT framework is used as a reference in identifying components that should exist in a flood management governance structure. This paper proposes a high level flood management governance collaborative environment incorporating the existing flood management components, as identified through reviews and field visits to several flood management sites.